Isotretinoin as a Possible Environmental Trigger to Autoimmunity in Genetically Susceptible Patients - Jocelyn Nugroho; Bahareh Schweiger (Case Reports in Pediatrics)
Introduction. Isotretinoin is commonly used to treat cystic acne. Definitive mechanisms of action for isotretinoin are not known though despite many side effects having been documented. Various case reports have noted autoimmune diseases succeeding isotretinoin treatment. Case Report. A 16-year-old female presents with symptoms of tremors, lack of focus, sleeplessness, emotional liability, bulging eyes, loose stools, heat intolerance, and missed menstrual periods. Symptoms manifested shortly after the patient finished a course of oral isotretinoin treatment for acne. Physical exam showed resting tremors, bilateral proptosis, hyperactivity, and rapid speech. A diagnosis of Graves’ Disease was made by correlating symptoms, physical exam findings, ultrasound, and positive family history of autoimmune thyroid disease. Conclusion. Emergence of autoimmune thyroid diseases depends upon genetic predisposition and environmental triggers. Mechanism of action for isotretinoin is not known but the drug may play a role in triggering autoimmunity in genetically susceptible individuals.